MARKET ORIENTATION PADA PT GUNUNG HIJAU MASARANG BERDASARKAN SKALA MARKOR - Alan R. Rombon; Leonardus R. Rengkung; Jen ., Tatuh (AGRI-SOSIOEKONOMI, 2018)
This study aims to know the Market Orientation (market intelligence, market intelligence dissemination, responsiveness of market intelligence). This research was conducted for three months from May until July 2017. The data used are primary data which is quantified by using Likert scale. The data taken by using survey method and use questioner to be distributed to 6 respondents in company. Questionnaires are used to identify market intelligence, market intelligence spread, responsiveness to market intelligence. Based on the results of research conducted at PT Gunung Hijau Masarang, the company's market orientation value was 67.29 percent. The company's market intelligence carried out customer service activities to know the consumer's response to the product. In the Market Intelligence Spread, Company companies understoodmarket integrations such as informally discussing competitor strategies, formal and informal discussions of needs. Whereas in the responsiveness of market intelligence the Company understood market orientation towards the response to market integrity. The company received complaints such as if there is a defectiveproduct, a change of packaging This is an opportunity for the company to correct the performance of the company as well as the service system like this makes it easier to encourage companies to more sharply looked at consumer needs.*jnkd*.